A kind of liquid-like MWCNT reinforcements for T1000 carbon fibre filament winding composites. (2nd August 2016) - Zhang, Qingjie; Li, Xiaochao; Liang, Shengbiao; Zhao, Xinfu; Sui, Gang; Yang, Xiaoping
Abstract: An intractable problem has been revealed that the resin matrix viscosity was rising obviously after the addition of solid nano-fillers involving all kinds of surface chemical modification, causing the degraded processing properties and defective structure in the polymer composites. Therefore, the application of nano-fillers in the filament winding processing of carbon fibre composites is severely limited, in which low initial viscosity of resin matrix is required under processing temperature to ensure the impregnation of the resin to fibres. In this study, a kind of liquid-like MWCNT reinforcements (L-MWCNTs) were fabricated and explored as nano-reinforcements for T1000 carbon fibre filament winding composites. Some technical means such as transmission electron microscopy and atomic force microscopy were used to analyze the dispersion state of L-MWCNTs and interfacial interaction of the resulting composites. The mechanical properties of carbon fibre filament winding composites were characterized through Naval Ordinance Laboratory-ring burst tests and interlaminar shear strength (ILSS) tests. The results showed that the L-MWCNTs can be uniformly dispersed in an epoxy matrix without deteriorating good processing performances for the filament winding composites. The resin matrix containing the L-MWCNTs exhibited a lower surface energy and better interface bonding with T1000 carbon fibre than that of the neat epoxy. Through the addition of 6 wt% L-MWCNTs, an enhancement of 15% in tensile strength, 28% in ILSS, as well as 14.8 °C in Tg was realized for T1000 carbon fibre composites. The L-MWCNTs can exhibit important application values as a nano-reinforcement for improving interfacial, mechanical and thermal properties of the existing carbon fibre composites.